Mechanization and the human desire for control in ghost in the shell and innocence. - Yap, Esther Lei Ling. (2009)
It is undeniably true that the desire to gain control of circumstances is inherent in humanity. Thus, the near futuristic world depicted in the animated films, Ghost in the shell and it's sequel, Ghost in the Shell 2: Innocence, directed by Mamoru Oshii, acutely reflects the fulfillment of humanity's desire to conquer the natural and physical laws of nature and death. This is achieved when humans reassemble themselves in various degrees, into cyborgs, which is a combination of machine and flesh. Other then reassembling themselves into mechanical 'pseudo-gods', cyborged-humans also gain quicker access to the virtual nexus of the Internet that permeates their entire society, which allows them to extend their sphere of control in society. However, as humans mechanize themselves in order gain physical empowerment and to be part of the network , this results in the separation of the original composition of the individual being into two distinct entities known as the 'ghost' and the 'body'. Hence, humans are ironically susceptible to control and subversion by external sources which includes the 'mechanical Other'. This eradicates the sense of freewill and causes the individual to be manipulated around like 'living marionettes'. As such, my thesis will ultimately unveil that fact that the endeavors of humanity to attain their former stature through the medium of technology and mechanization only turns them into the victims of their own actions and exposes the monstrous egocentricity in their flawed nature.